Nutrition Patterns and Iron Supplementation in the Prevention of Anaemia in Adolescent Girls - Heldalia Faiza Putri; Cesa Septiana Pratiwi; Ismarwati Ismarwati (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Anaemia among adolescent girls remains a major public health problem in developing countries and is associated with inadequate dietary intake and low adherence to iron supplementation. Despite numerous studies examining dietary patterns and iron supplementation, evidence regarding the nutritional, behavioural, and environmental factors influencing anaemia prevention has not been comprehensively synthesised. This study aimed to map the available scientific evidence on nutrition patterns and iron supplementation in the prevention of anaemia among adolescent girls. Method: A scoping review was conducted following the Arksey and O’Malley framework. Literature searches were performed in PubMed, ScienceDirect, Wiley Online Library, and Google Scholar databases for studies published between 2020 and 2025. Articles were screened according to predefined inclusion and exclusion criteria. Data were extracted, charted, and synthesised thematically. Of the 317 articles identified, 11 studies met the eligibility criteria and were included in the review. Result: The review identified four major themes: behavioural and psychosocial factors, nutritional patterns and nutrient intake, adherence to iron supplementation, and educational interventions. Low intake of iron, protein, and vitamin C, unhealthy dietary habits, and poor adherence to iron-folic acid supplementation were consistently associated with a higher risk of anaemia. Knowledge, motivation, attitudes, self-efficacy, and support from schools and families influenced preventive behaviours and supplementation adherence. Educational interventions improved knowledge and adherence; however, their impact on haemoglobin levels was inconsistent across studies. Conclusion: Anaemia prevention among adolescent girls requires an integrated approach combining dietary improvement, iron supplementation, behavioural interventions, and supportive environments. Strengthening nutrition education, promoting adherence to supplementation programmes, and implementing school-based health promotion strategies are recommended to reduce the burden of anaemia among adolescent girls.